Pig as a reservoir of CRISPR type TST4 Salmonella enterica serovar Typhimurium monophasic variant during 2009–2017 in China - Xiaolei Xie; Zhenyu Wang; Kai Zhang; Yang Li; Yachen Hu; Zhiming Pan; Xiang Chen; Qiuchun Li; Xinan Jiao (Emerging Microbes and Infections)
CRISPR-based typing was performed to subtype isolates of S. Typhimurium and its monophasic variant Salmonella 4,[5],12:i:- from humans and animals between 2009 and 2017 in China. CRISPR typing classified all isolates into two lineages and four sub-lineages. All isolates from Lineage II and Lineage IB-1 were Salmonella Typhimurium. All of Salmonella 4,[5],12:i: – isolates were distributed in Lineage IA and Lineage IB-2, which all belonged to ST34 by MLST typing. Only Lineage IB-2 contained ST34 isolates from both Salmonella Typhimurium and Salmonella 4,[5],12:i:-. Among the isolates of ST34, TST4 was identified as the most common CRISPR type representing 86.5% of Salmonella 4,[5],12:i:- and 14.5 % of Salmonella Typhimurium mainly from pigs and humans. This study demonstrated that TST4-ST34 isolates were predominant in Salmonella 4,[5],12:i:-, and pig was the main reservoir for Salmonella 4,[5],12:i:- in China, which might have the potential to transmit to humans by pig production.